The dilemma of delayed presentation in breast cancer: a perspective from the Radiology department of a developing country of Asia - Gul, Palwasha; Gul, Pari; Jogezai, Shama; Gul, Khanda; Parveen, Tanzila (International Journal Of Community Medicine And Public Health, 2019)
Background: In Asia, Pakistan has the highest incidence of breast cancer with 1 in 8 women will develop breast cancer at some stage of their life. Delays in presentation and diagnosis are major determinants of breast cancer survival, but these have not been comprehensively investigated in Pakistan. Methods: A cross-sectional study was done from June 2017 till October 2018 at Radiology department of Bolan medical complex hospital in Quetta, Pakistan. Patients with breast cancer above the age of 18 and below 70 years were interviewed who were diagnosed with breast cancer. The time interval between self-detection and deciding to seek care was defined as delayed if the woman presented to a health care professional three months or more after detecting an abnormality Results: A total of 86 breast cancer patients fulfilling the criteria were included in the study. Of these, 34% presented to physician within 3 months of appearance of symptoms, 68% patients presented with a delayed of more than 3 months. Presentation delay was due to financial issues which were seen in 30 patients. 18 patients (20.9%) showed delayed to due difficulty in reaching hospitals, 16 patients (18%) stated delay due to prior use of alternative therapies. Embarrassment and spiritual belief constituted 4.6% cases. 51% and 36% presented with stage III and IV disease out of which majority belonged to poor socio-economic status. Conclusions: The findings suggest that majority of the patients with breast cancer presented late and this has significant effect on their disease prognosis. Most cases of breast cancer presented in advanced stage probably due to poor economic status, difficulty in reaching hospital, illiteracy and negligence by patient or family.